Defective Interferon-Gamma Production Is Common in Chronic Pulmonary Aspergillosis. (29th November 2021) - Colombo, Stefano A P; Hashad, Rola; Denning, David W; Kumararatne, Dinakantha S; Ceron-Gutierrez, Lourdes; Barcenas-Morales, Gabriela; MacDonald, Andrew S; Harris, Chris; Doffinger, Rainer; Kosmidis, Chris
Abstract: Background: Immune defects in chronic pulmonary aspergillosis (CPA) are poorly characterized. We compared peripheral blood cytokine profiles in patients with CPA versus healthy controls and explored the relationship with disease severity. Methods: Interferon-gamma (IFNγ), interleukin (IL)-17, tumor necrosis factor-α, IL-6, IL-12, and IL-10 were measured after in vitro stimulation of whole blood with lipopolysaccharide (LPS), phytohemagglutinin, β-glucan, zymosan (ZYM), IL-12 or IL-18, and combinations. Clinical parameters and mortality were correlated with cytokine production. Results: Cytokine profiles were evaluated in 133 patients (57.1% male, mean age 61 years). In comparison to controls, patients with CPA had significantly reduced production of IFNγ in response to stimulation with β-glucan + IL-12 (312 vs 988 pg/mL), LPS + IL-12 (252 vs 1033 pg/mL), ZYM + IL-12 (996 vs 2347 pg/mL), and IL-18 + IL-12 (7193 vs 12 330 pg/mL). Age >60 (hazard ratio [HR], 1.71; 95% confidence interval [CI], 1.00–2.91; P = .05) and chronic obstructive pulmonary disease (HR, 1.69; 95% CI, 1.03–2.78; P = .039) were associated with worse survival, whereas high IFNγ production in response to beta-glucan + IL-12 stimulation (HR, 0.48; 95% CI, .25–0.92; P = .026) was associated with reduced mortality. Conclusion s: Patients with CPA show impaired IFNγ production in peripheral blood in response to stimuli. Defective IFNγ production ability correlates with worse outcomes. Immunotherapy with IFNγ could be beneficial for patients showing impaired IFNγ production in CPA. Abstract : Using whole blood stimulation with innate agonists and polyclonal T-cell stimulation, we demonstrate defects in the Th1 and Th17 pathways in patients with chronic pulmonary aspergillosis. IFNγ supplementation may be beneficial for patients with reduced IFNγ production.